2018
DOI: 10.1177/1553350618799786
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Neuromonitoring During Thyroid Surgery: The Effect of Surgical Positioning

Abstract: Intraoperative neuromonitoring during thyroid surgery has been used to successfully prevent permanent neurological injury by early identification of anatomical variants. Proper interpretation of neuromonitoring data requires knowledge of what factors might affect the data. In this study, we examined the effect of surgical positioning on the latency and amplitude of neural recordings made from the vocalis muscle during thyroid surgery. A retrospective review was performed of 145 patients who underwent thyroid s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…16,21 Our previous study showed a significant decrease in right RLN amplitude with a TAA compared to a TCA. 15 However, in our current study, with a larger study population, there was no difference in RLN amplitude between approaches. Furthermore, a TAA was not associated with decreased amplitude or increased latency of the vagus nerve on either side, even though there was a statistically significant change in vagus nerve location post-positioning bilaterally.…”
Section: Discussioncontrasting
confidence: 68%
See 4 more Smart Citations
“…16,21 Our previous study showed a significant decrease in right RLN amplitude with a TAA compared to a TCA. 15 However, in our current study, with a larger study population, there was no difference in RLN amplitude between approaches. Furthermore, a TAA was not associated with decreased amplitude or increased latency of the vagus nerve on either side, even though there was a statistically significant change in vagus nerve location post-positioning bilaterally.…”
Section: Discussioncontrasting
confidence: 68%
“…The aim of this study was to build upon our previous study to help define expected IONM measurements during transaxillary thyroid and parathyroid surgery. 15 In both our previous and current studies, mean evoked latency of the right vagus nerve was significantly decreased in TAA procedures. In our current study, this difference was also observed when analyzing total thyroidectomy and right hemithyroidectomy separately.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations